Tren dan Tantangan dalam Era Keperawatan Digital: Apa yang harus diantisipasi perawat - Grace Fresania Kaparang; Denny Maurits Ruku (LITERATUS, 2022)
Welcome to digital era. Nursing has significantly impacted by the advancing technology as it put a firm stronghold of most inhabitants of earth. The study is a literature review with narrative review method through thematic analysis on the digital trends and its challenges for nurses followed by recommendations to tackle the challenges. 15 articles were found from Google Scholar using the keywords of “trends in digital nursing era” and furthermore the trends, challenges and recommendations were drawn to provide nurses the ideas of how to tackle the challenges were discussed. It was found that there are three themes regarding the trends and challenges which were increasing educated or hoax-loaded client; increasing demand of technologically savvy nurses and rise of health informatics; and nursing online education increment. For the recommendations it was suggested that in order that nurses may react properly in this technology advancement era where more educated clients are increasingly found, nurses should keep on being updated with current practices and should know what the best and current implementation and proper care to the clients is. Nurses also should do fact checking and make sure that the interventions are evidence-based practice and not to believe all informations provided by online websites by continue to research and prove and reprove, then they may properly educate the clients, especially those who are hoax-loaded mind. Furthermore, nurses should be more prepared by polishing their technology skills, paying attention to health informatics field, and considering further education to be pursued. In terms of online nursing education, the risk-benefit ratio as well as the pros and cons should be carefully considered before pursuing the course to increase the competency and knowledge in this millenial era effectively and efficiently.